THE EFFECT OF PRACTICUM METHOD ON REPRESENTATION ABILITY AND COGNITIVE LEARNING OUTCOMES - Darlen Sikumbang; Dewi Lengkana; Rita Foorantika (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
The existence of laboratory activities in or outside the room can facilitate students in visualizing the imagination to be real. This study aims to determine the effect of using practicum methods on the students' representation ability and cognitive learning outcomes on the subject matter Classification of Living Things. This research was conducted at Junior High School 26 Bandar Lampung. The method uses a quasi-experimental method with Pretest-Posttest Non-Equivalent Control Group Design. A random sampling technique took the sample in this study, and the research subject uses class VII A as experiment class and VII B as a control class. The data in this study are quantitative data that were analyzed using the Independent sample t-test. Based on the results of this study, the effect of practicum methods on the students' representation ability is level 1, and 2 before the treatment then increases to levels 3, 4, and 5 after the practicum with the student answers that have made elements representation such as tables, graphs, icons, and images. Therefore, practicum methods can be used by science educators to facilitate students in conceptual understanding by using elements of representation.